Myocardium Assessment by Relaxation along Fictitious Field, Extracellular Volume, Feature Tracking, and Myocardial Strain in Hypertensive Patients with Left Ventricular Hypertrophy - Seyed Amir Mirmojarabian; Eveliina Lammentausta; Esa Liukkonen; Lauri Ahvenjärvi; Juhani Junttila; Miika T. Nieminen; Timo Liimatainen (International Journal of Biomedical Imaging)
Background. Previous research has shown impaired global longitudinal strain (GLS) and slightly elevated extracellular volume fraction (ECV) in hypertensive patients with left ventricular hypertrophy (HTN LVH). Up to now, only little attention has been paid to interactions between macromolecules and free water in hypertrophied myocardium. Purpose. To evaluate the feasibility of relaxation along a fictitious field with rank 2 (RAFF2) in HTN LVH patients. Study Type. Single institutional case control. Subjects. 9 HTN LVH (age, 69±10 years) and 11 control subjects (age, 54±12 years). Field Strength/Sequence. Relaxation time mapping (T1, T1ρ, and TRAFF2 with 11.8 μT maximum radio frequency field amplitude) was performed at 1.5 T using a Siemens Aera (Erlangen, Germany) scanner equipped with an 18-channel body array coil. Assessment. ECV was calculated using pre- and postcontrast T1, and global strains parameters were assessed by Segment CMR (Medviso AB Co, Sweden). The parametric maps of T1ρ and TRAFF2 were computed using a monoexponential model, while the Bloch-McConnell equations were solved numerically to model effect of the chemical exchange during radio frequency pulses. Statistical Tests. Parametric maps were averaged over myocardium for each subject to be used in statistical analysis. Kolmogorov-Smirnov was used as the normality test followed by Student’s t-test and Pearson’s correlation to determine the difference between the HTN LVH patients and controls along with Hedges’ g effect size and the association between variables, respectively. Results.TRAFF2 decreased statistically 83±2 ms vs 88±6 ms,P<0.031, and global longitudinal strain was impaired (GLS, −14±3 vs−18±2,P<0.002) in HTN LVH patients compared to the controls, respectively. Also, significant negative correlation was found between TRAFF2 and GLS r=−0.53,P<0.05. Data Conclusion. Our results suggest that TRAFF2 decrease in HTN LVH patients may be explained by gradual collagen accumulation which can be reflected in GLS changes. Most likely, it increases the water proton interactions and consequently decreases TRAFF2 before myocardial scarring.